A releasable disulfide-linked peptide tag facilitates the synthesis and purification of short peptides. Issue 19 (10th February 2020) - Wu, Yuteng; Zorzi, Alessandro; Williams, Jack; Heinis, Christian
Abstract : A peptide synthesis and purification strategy that omits a throughput-limiting chromatographic purification step offers access to large macrocyclic compound libraries. Abstract : Combinatorial cyclization of hundreds to thousands of random linear peptides by structurally diverse chemical linkers offers access to large macrocyclic compound libraries. A bottleneck in the development of such libraries is the preparation of large numbers of short random linear peptides. Herein, we present a tag-based strategy that is not dependent on a throughput-limiting chromatographic purification step and thus enables parallel production of short peptides. In brief, peptides are synthesized on solid phase as conjugates with a disulfide-linked Cys-Gly-Arg-Trp tetra-peptide tag. The charged arginine residue in the tag allows for purification of the peptides by diethyl ether-precipitation and the tryptophan allows for quantification of the product by absorption measurement. Addition of a reducing agent releases the short peptides from the tag. The released sulfhydryl group in the peptide can readily be used for cyclization of the peptide library with bis-electrophilic linker reagents.